Clinicopathologic classification of diabetic nephropathy and expression of Ang-2 in renal tissues - WEIZhi-min; MARui-xia; LIU Li-qiu (Linchuang shenzangbing zazhi)
Objective To investigate the clinical value of new pathological classification of diabetic nephropathy(DN) by published Research Committee of the Renal Pathology Society in 2010,and explore the expression and signification of angiopoietin-2(Ang-2) in renal tissues.Methods Renal biopsy was performed on 57 patients with impaired renal function.The tissues were split to be stained by HE,PAS,Masson and PASM for light microscope and stained by IgA,IgG,IgM and C3 for immunofluorescence microscope,and for electron microscope also.All cases were re-classified according to the new pathological classification for DN,and the relationship between the different types of DN and the tubulointerstitial injury was observed.The Ang-2 expression in the renal tissues was detected by immunohistochemistry.Results Before the 2010,19 patients were diagnosed as having DN.After re-analysis according to the new pathological classification,the patients diagnosed with DN were increased to 22,while 32 patients were diagnosed as DN after 2010.In these 54 DN patients,2 cases were classified as type Ⅰ,5 as type Ⅱ a,5 as type Ⅱ b,37 as type Ⅲ and 5 as type Ⅳ.Twenty patients had mild interstitial injury,25 had midrange interstitial injury,and 9 had severe interstitial injury.For all DN research subjects,Ang-2 was detectable to varying degrees in capillaries clump of glomeruli and endothelial cells of blood vessels.The Ang-2 staining was observed in the very early stage of DN.Conclusions The new pathological classification of DN can decrease the misdiagnosis rate and attract more attention to interstitial damage and vessel damage in DN.And for diabetic mellitus patients,Ang-2 detected by renal biopsy could be used for contributing to the early diagnosis and would be beneficial for patients’ individual treatment.